Conversion of methyl ethyl ketone (MEK) to valuable chemicals over multifunctional supported catalysts - Al-Auda, Zahraa Fadhil Zuhwar (Kansas State University, 2018)
The present work describes the conversion of bio-derived methyl ethyl ketone (MEK) into different useful chemicals. The first part discusses the direct conversion of MEK to butene over supported copper catalysts (Cu-Al₂O₃, Cu-zeolite Y sodium (Cu-ZYNa) and Cu-zeolite Y hydrogen (Cu-ZYH)) in a fixed bed reactor. In this reaction, MEK is hydrogenated to 2-butanol over metal sites, and further dehydrated on acid sites to produce butene. Experimental results showed that the selectivity of butene was the highest over Cu-ZYNa, and it was improved by finding the optimum reaction temperature, hydrogen pressure and the percentage of copper loaded on ZYNa. The highest selectivity of butene (97.9%) was obtained at 270 °C and 20 wt% Cu-ZYNa. Over Cu-Al₂O₃, the selectivity of butenes was less than Cu-ZYNa since subsequent hydrogenation of butene occurred to produce butane. It was also observed that with increasing H₂/MEK molar ratio, butane selectivity increased. However, when this ratio was decreased, hydrogenation of butene was reduced, but dimerization to C₈ alkenes and alkane began to be favored. The main products over 20% Cu-Al₂O₃ were butene and butane, and the maximum selectivity of butene (87%) was achieved at an H₂/MEK molar ratio of five. The lowest selectivity of butene was obtained using Cu-ZYH, reaching ~40%. It was found that the amount of acidity in Cu-ZYH is much higher than in Cu-ZYNa (from (NH₃-TPD) measurements). This could have caused the selectivity of butene to decrease as a result of dimerization, oligomerization and cracking reactions. The second part describes the conversion of MEK to higher ketones in one step using a multifunctional catalyst having both aldol condensation (aldolization and dehydration) and hydrogenation properties. 15% Cu supported zirconia (ZrO₂) was investigated in the catalytic gas phase reaction of MEK in a fixed bed reactor. The results showed that the main product was 5-methyl-3-heptanone in addition to 5-methyl-3-heptanol and 2-butanol with side products including other heavy products (C₁₂ and up). The effects of temperature and the molar ratio of reactants (H₂/MEK) on overall product selectivity were studied. It was found that with increasing temperature, the selectivity to C₈ ketone increased, while selectivity to 2-butanol decreased. The hydrogen pressure plays significant role on the selectivity of products. It was observed that with increasing the H₂/MEK molar ratio, 2-butanol selectivity increased due to hydrogenation reaction while decreasing this ratio leads to increasing aldol condensation products. In addition, it was noted that both conversion and selectivity to the main product increased using a low loading percentage of copper, 1% Cu-ZrO₂. The highest selectivity of 5-methyl-3-heptanone (~63%) was obtained at temperatures around 180 °C and a molar ratio of H₂/MEK of 2. Other metals (Ni, Pd and Pt) supported on ZrO₂ also produced 5-methyl 3-heptanone as the main product with slight differences in selectivity, suggesting that a hydrogenation catalyst is important for making the C₈ ketone, but the exact identity of the metal is less important. The third part discusses the conversion of C₈ ketones to C₈ alkenes and C₈ alkane over a catalyst consisting of a transition metal (Cu or Pt) loaded on alumina (Al₂O₃). These bifunctional catalysts provide both hydrogenation and dehydration functionalities. The main products over 20% Cu-Al₂O₃ were a mixture of 5-methyl-3-heptene, 5-methyl-2-heptene and 3-methyl heptane. However, using 1% Pt-Al₂O₃ the major product was 3-methyl heptane with a selectivity reaching over 97% and a conversion of 99.9 %. Both temperature and the hydrogen pressure play an important role on the conversion of C₈ ketone as well as the selectivity of products (C₈ alkenes and C₈ alkane). Over 20% Cu-Al₂O₃, it was observed that increasing the reaction temperature led to an increase in the selectivity to C₈ alkane as a result of hydrogenation of the C₈ alkene. Also, it was observed that with an increase in H₂/C₈ ketone molar ratio, C₈ alkane selectivity increased. However, when this ratio was decreased, the further hydrogenation of C₈ alkene to C₈ alkane was reduced. The highest selectivity of C₈ alkene (81.7%) was obtained at 220 °C and a H₂/C₈ ketone molar ratio of 2. In addition, an experiment was carried out using a low loading percentage of copper, and it was noted that both conversion and selectivity to the main products decreased over 1% Cu-Al₂O₃. Over 1% Pt-Al₂O₃, C₈ alkane was the major product with different temperatures indicating that further hydrogenation of C₈ alkene was promoted on 1% Pt-Al₂O₃. At low temperature, for both Cu-Al₂O₃ and Pt-Al₂O₃, significant amounts of C₈ alcohols are formed because subsequent reactions do not proceed at a fast enough rate. Also using 1% Pt-Al₂O₃, the main product selectivity is still C₈ alkane with all H₂/C₈ ketone ratios.
Keywords: Methyl Ethyl Ketone; Bifunctional Catalyst; Multifunctional Catalyst; Butene